The mechanism of physical exercises increases heat shock protein 70 (HSP70) (a systematic review) - N. Ayubi; J.C. Wibawa; C. Callixte (Medičnì Perspektivi, 2024)
This study aimed to analyze physical exercise in increasing the expression of heat shock protein 70 (HSP70). This research is a systematic review involving searches from journal databases such as Pubmed, Web of Science, and Science Direct. Before starting the search, the study determines inclusion and exclusion criteria. The inclusion criteria were articles that discussed oxidative stress, physical exercises, and heat shock protein 70 (HSP70), and were published over the last five years (2018-2023). Meanwhile, the articles were excluded if they were published in non-reputable journals or were not indexed by Scopus and Web of Science. A total of 3211 articles from the Science Direct, Pubmed, and Web of Science databases were initially identified. Among them, ten articles met the inclusion criteria and thus were selected and analyzed for this systematic review. For standard operations, this study follows the preferred reporting items for systematic reviews and meta-analyses (PRISMA) assessment. The results showed that physical exercises played a certain role in increasing HSP70 expression as a physiological reaction to exercises. The increase in HSP70 is good as it can reduce and prevent inflammation, which reduces cell damage due to physical stress. Additionally, HSP70 increases catalase and superoxide dismutase, the processes that can reduce reactive oxygen species (ROS) caused by physical exercises. This enzyme is also important in protein optimization based on requirements. Therefore, we recommend doing physical exercises to improve health and avoid degenerative diseases.